CHARACTERISTICS OF DIELECTRIC BARRIER DISCHARGE (DBD) AS AN OZONE GENERATOR REACTOR - Gede Wiratma Jaya; Muhammad Nur Nur; Andhika Dwi Anggara; Nofrita Angelina Metungku; Andi Wibowo Kinandana; Intan Zahar; Alfatihatuz Zulfah Zain (Jurnal PPI Dunia, 2018)
Ozone is a gas formed from three oxygen atoms that are highly reactive and unstable compared tooxygen. Ozone can be generated by using a dielectric barrier discharge (DBD) generator. To know theability of DBD reactor in producing ozone performed a characterization. Characterization is done bymeasuring the electrical current, electrical voltage, observing the plasma discharge, charge mobility,and ozone concentration. In this research using DBD reactor derived from the development of researchTeaching Industry of Diponegoro University. DBD reactor containof pyrex glass material as adielectric barrier and parabolic wire made of aluminum as inner and outside electrodes in the dielectricbarrier. DBD reactor was generated using high AC voltage of 2, 4, 6, 8, 10 and 12 kV and air flow rateis 10 L/min. The characterization results show that the higher the voltage can results increases ofelectrical current, for a discharge plasma produces a purplish color as a result of ionization process onthe electrode. The calculation of charge mobility is 9.71 x 10−3m2V−1s−1and the lowest and highestozone concentration is 80 ppm and 280 ppm, respectively. In the future, application of DBD reactorhas been characterized can be usedfor ozone gas production as food preservatives, improvement of theenvironmental quality of aquaculture and as an industrial and medical waste treatment system.